Students’ Self-Efficacy And Technology Acceptance Of Nicenet In Efl Classroom - Rezki, Anita; Sailan, Zalili; Alberth, Alberth (Halu Oleo University, 2016)
The objective of this study were: to measure students’ Self Efficacy in Nicenet in EFL Classroom, to investigate whether or not there was any difference in terms of technology acceptance and Self-Efficacy between male and female students as well as between students’ having difference experience with Nicenet, to measure students’ technological acceptance of Nicenet in EFL Classroom and to investigate students’ perception about the benefits and the drawbacks of Nicenet. This study adopted a mixed method design which employed both qualitative and quantitative research design. Instruments of the study were questionnaire, interview guideline and relevant documents. The study was conducted at the English Language Education study program, in Halu Oleo Univesity, involving students who had joined and experienced the use of Nicenet in their class. Fifty students participated in this study by filling out a questionnaire and 8 students were interviewed to obtain more information related to their response in questionnaire. Result of the study showed that generally the students could be grouped into two levels of Self-Efficacy; a high level and medium level. Regarding to the second research question, it was discovered that there was no significant differences between male and female as well as between Nicenet experiences. A slightly contradictory result found in the students’ responses to the questionnaire and interview which were set out to seek positive answer to the third research questions. While generally the students expressed their positive acceptance to technology, they gave different information in the interview. As far as the fourth research question was concerned, more benefits and drawbacks of Nicenet had been revealed based on the students’ responses to open-ended questions and interview.